2009
DOI: 10.1029/2008jd010636
|View full text |Cite
|
Sign up to set email alerts
|

River basins as groundwater exporters and importers: Implications for water cycle and climate modeling

Abstract: [1] The groundwater reservoir and its interaction with surface water facilitate lateral transport of continental water and energy. Current climate models do not account for long-distance groundwater flow between model cells but route the atmospheric surplus (precipitation (P) minus evapotranspiration (ET)) directly to stream discharge within a model grid cell. We ask how much water exits a river basin without ever passing through its surface outlet? What are the climatologic and geologic factors influencing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
225
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 167 publications
(238 citation statements)
references
References 80 publications
13
225
0
Order By: Relevance
“…The difficulty of using the surface observation to improve root zone soil moisture has been reported by Walker et al (2001) and Houser et al (1998) who showed that soil moisture estimates in the lower soil zone deteriorated with the assimilation of surface observations. As pointed out by Walker et al (2001) that data assimilation could only achieve what model physics is capable of delivering, the failure of the conventional EnKF in updating the lower layers, as shown in this study, is a result of inappropriate model physics.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The difficulty of using the surface observation to improve root zone soil moisture has been reported by Walker et al (2001) and Houser et al (1998) who showed that soil moisture estimates in the lower soil zone deteriorated with the assimilation of surface observations. As pointed out by Walker et al (2001) that data assimilation could only achieve what model physics is capable of delivering, the failure of the conventional EnKF in updating the lower layers, as shown in this study, is a result of inappropriate model physics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to preserving mass, Eq. (6) avoids updating the lower layers with the conventional EnKF which has been shown to yield undesired increments due to inappropriate model physics (Houser et al, 1998;Walker et al, 2001). Preserving water mass does not necessarily lead to improved soil moisture estimates in the lower layers, but Eq.…”
Section: Data Assimilation Methodsmentioning
confidence: 99%
See 3 more Smart Citations